Ionic Liquid-Intercalated Montmorillonite Interfacial-Reinforced Polymer Composite Scaffold. (8th February 2023) - Li, Dongying; Li, Pin; Wang, Haoyu; Du, Haocheng; Liu, Lixuan; Li, Bin; Xu, Yong; Li, Mengqi; Zhou, Yanrong
Abstract : Montmorillonite is often used to enhance the mechanical and biological properties of polymer materials, but the weak interaction between the enhanced phase and the matrix limits the enhancement effect. Herein, ionic liquids were introduced as interfacial compatibilizer to improve the dispersion of the enhanced phase in the matrix and interaction between them, and a composite scaffold with enhanced mechanical properties was prepared by selective laser sintering. Specifically, the positively charged terminations of 1- n -butyl-3-methylimidazolium in ionic liquids were anchored to the montmorillonite interlayer domain under electrostatic action. At the same time, the long carbon chain at the other end extends in the opposite direction to increase the layer spacing of the montmorillonite, which provides enough space for the intercalation of the polyetheretherketone molecular chain. First, the blue shift of the diffraction peak in the small-angle X-ray diffraction pattern proves the successful insertion of ionic liquids into the interlayered domain of montmorillonite. In addition, the compression test results show that the compressive strength of the modified composite scaffold was increased by 23%, reaching 31.53 MPa. Besides, the composite scaffold exhibits good biomineralization capacity, which may be attributed to ion modification providing more apatite-shaped nucleation sites. These results suggested that the method of modifying inorganic fillers with ionic liquids to enhance mechanical properties and promote mineralization may be an effective means for bone scaffold modification.